Actor-Network Theory and the Practice of Aviation Archaeology. Issue 1 (January 2015) - Deal, Michael; Daly, Lisa M.; Mathias, Cathy
<x content-type="archive" xml:space="preserve">Abstract</x> World War II aviation archaeology is a dynamic subfield of conflict archaeology, which has developed through the need to conserve twentieth-century military heritage resources. Like battlefield archaeology (Pollard and Banks, 2005: iii–vii), it has only recently emerged as a credible area of academic study. Theoretical development in both areas has been dominated by a military, historical-particularist viewpoint, which often ignores the role of society in warfare. Actor-network theory, which stresses the link between society and technology, provides an opportunity to broaden the theoretical perspective of aviation archaeology research. Recent archaeological work at a downed USAAF aircraft site near Gander, Newfoundland, is presented as a case study to illustrate the enlistment of a network of stakeholders, material culture, and textual and audio-visual evidence in the interpretation of a single site.